The Relationship Between Cigarette Consumption And Poverty: Analysing The Role Of Price - Suwardi Dwi Pramita; Khoirunurrofik Khoirunurrofik (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Poverty has been a global concern until recently. In Indonesia, the poverty rate will reach 9.57 per cent in 2023 or at least 26 million people below the poverty line. A phenomenon occurs in poor communities in Indonesia where half of the households spend money on cigarettes. Cigarette consumption burdens households through consumption costs as well as health costs and reduced household productivity, which can affect the welfare of smoker households. Conversely, environmental factors, especially in poor communities, also influence cigarette consumption habits. This study aims to examine the relationship between cigarette consumption and poverty. For this reason, the instrumental variable method is used to avoid endogeneity bias due to reverse causality when analysing the relationship between cigarette consumption and poverty. Cigarette price is used as the instrument variable. The data used in the study is pooled cross section data from the National Socio-Economic Survey from 2014 to 2021. The results of the analysis show a significant negative relationship of cigarette prices to household cigarette consumption and cigarette consumption increases the probability of households being poor.